The Politics of Emotion - Silleras-Fernandez, Nuria (Cornell University Press, 2024)
The Politics of Emotion – Contents – Acknowledgments – List of Abbreviations – Note on Names and Translations – The Politics of Emotion: An Introduction – 1. Love and Excess/Love as Excess – 2. Regulating Death, Grief, and Consolation – 3. Love and Sexuality as Power: Isabel of Portugal, Queen of Castile – 4. Contested Agency: Isabel of Portugal and Saint Beatriz da Silva – 5. Portugal, 1491: A Princess and a Kingdom in Mourning – 6. Consoling the Princess of Portugal, or the Price of Remarriage – 7. Juana and Isabel: The Tale of a Prodigal Daughter – 8. Madness in the Age of Empire: Juana I, Queen of Castile – Conclusion: Love and Death and the Politics of Emotion – Bibliography – Index.
Description based on publisher supplied metadata and other sources
Keywords: Isabel; Juana; Women; Emotions; Mental illness; Europäische Geschichte: Mittelalter; Gender Studies: Frauen und Mädchen; Gender studies: women; HISTORY / Medieval; LITERARY CRITICISM / Medieval; Literary studies: classical; early & medieval; Literaturwissenschaft: Antike und Mittelalter; Mittelalterlicher Stil; SOCIAL SCIENCE / Women's Studies